2010
DOI: 10.1186/1477-3155-8-13
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and mechanisms of quantum dot nanoparticle cellular uptake

Abstract: BackgroundThe rapid growth of the nanotechnology industry and the wide application of various nanomaterials have raised concerns over their impact on the environment and human health. Yet little is known about the mechanism of cellular uptake and cytotoxicity of nanoparticles. An array of nanomaterials has recently been introduced into cancer research promising for remarkable improvements in diagnosis and treatment of the disease. Among them, quantum dots (QDs) distinguish themselves in offering many intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 40 publications
4
89
2
1
Order By: Relevance
“…It should be noted that phases 1 and 2 of quantum dot distribution in the cells were found earlier in the studies reported by Hoshino et al, 16 Clift et al, 20 and Jiang et al, 19 Kelf et al, 14 Williams et al, 15 and Corsi et al, 17 which showed formation of vesicular structures spread in the cytoplasm corresponding to phase 2. Phase 3, ie, localization of vesicular structures in the perinuclear region, was described by Zhang et al 22 and Xiao et al, 23 and reviewed by Parak et al 33 Phase 4 resembles the data on formation of multivesicular body-like structures and their redistribution in cytoplasm presented by Yuan et al 18 and Jiang et al 19 However, there has been no presentation of an overall picture illustrating the time-dependent nature of natural uptake and distribution of nontargeted negatively charged quantum dots in living cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that phases 1 and 2 of quantum dot distribution in the cells were found earlier in the studies reported by Hoshino et al, 16 Clift et al, 20 and Jiang et al, 19 Kelf et al, 14 Williams et al, 15 and Corsi et al, 17 which showed formation of vesicular structures spread in the cytoplasm corresponding to phase 2. Phase 3, ie, localization of vesicular structures in the perinuclear region, was described by Zhang et al 22 and Xiao et al, 23 and reviewed by Parak et al 33 Phase 4 resembles the data on formation of multivesicular body-like structures and their redistribution in cytoplasm presented by Yuan et al 18 and Jiang et al 19 However, there has been no presentation of an overall picture illustrating the time-dependent nature of natural uptake and distribution of nontargeted negatively charged quantum dots in living cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,12 Analysis of results presented in the literature reveals a very wide range of values for quantum dot internalization parameters, in particular, uptake time and intracellular localization. [13][14][15][16][17][18][19][20][21][22][23][24] This could be due to time-dependent changes in accumulation and intracellular distribution of quantum dots taking place even in a single cell line. The interpretation of results is even more complicated in the case of in vivo studies where the quantum dots would be internalized by different types of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Neutral or negatively charged QDs are only weakly bound to the lipid bilayer and thus are less readily taken up. 25 Given their size (4À5 nm in radius), QDs cross the plasma membrane primarily through pinocytosis, a distinct set of endocytosis mechanisms, chiefly responsible for the uptake of cell nutrients and other small particles (<100 nm). The contribution of each endocytosis pathway can be assessed using inhibitors that suppress specific internalization processes.…”
mentioning
confidence: 99%
“…However, differently from the liposomes that irreversibly leaked ( It must be noted that nonspecific passive delivery of QDs, though noninvasive and supposedly not compromising cell integrity and viability, completely relies on endocytosis. 61,62 However, similar QDs from clathrin-coated pits can be destined for different fates after internalization: sent back to the cell surface, trafficked toward a degradative fate in endosomes and lysosomes, or to the perinuclear recycling endosomal compartment, depending on cell phenotype. 63 This means that internalization and trafficking of QDs, though highly controlled by the cell, can be manipulated by choosing proper targeting ligands.…”
mentioning
confidence: 99%